2013
DOI: 10.1002/micr.22097
|View full text |Cite
|
Sign up to set email alerts
|

Safety of intra‐operative vasopressor in free jejunal flap reconstruction

Abstract: The intra-operative use of vasopressors is safe in free jejunal flap reconstruction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
37
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(39 citation statements)
references
References 16 publications
(18 reference statements)
2
37
0
Order By: Relevance
“…However, recently published articles have studied patients receiving intraoperative vasopressors during free flap reconstruction of the head and neck, as well as breast, and have found no significant increase in flap related complications. Two of these studies reported that these doses of vasopressors were given as intermittent boluses; the other three did not report on the duration or rate of the vasopressor administration. None have addressed vasopressor use extending into the postoperative period, when flaps may become more sensitive to vasoactive agents …”
Section: Casementioning
confidence: 99%
“…However, recently published articles have studied patients receiving intraoperative vasopressors during free flap reconstruction of the head and neck, as well as breast, and have found no significant increase in flap related complications. Two of these studies reported that these doses of vasopressors were given as intermittent boluses; the other three did not report on the duration or rate of the vasopressor administration. None have addressed vasopressor use extending into the postoperative period, when flaps may become more sensitive to vasoactive agents …”
Section: Casementioning
confidence: 99%
“…In contrast to these pervasive attitudes concerning vasopressors in free tissue transfer, multiple experimental and clinical studies have demonstrated increased flap blood flow with the use of various vasoactive medications [18][19][20][21][22] and no overall effect on flap outcomes. [22][23][24][25][26][27][28][29][30][31] The purpose this study is to address the following question: among patients undergoing head and neck free flap reconstruction, does the use of vasoactive medication intraoperatively, as compared with no use, increase the rates of free flap failure and complications? We hypothesize that the rates of free flap failure and complications in subjects receiving vasopressors intraoperatively during head and neck microsurgical reconstruction are equivalent to those not receiving vasopressors.…”
mentioning
confidence: 99%
“…1,2 Despite the negative attitudes toward the use of vasopressors during free flap reconstruction, multiple studies have documented a high prevalence of their use intraoperatively (52-82%), and overall lack of effect on ultimate flap outcomes. [3][4][5][6][7][8] We report two cases of free latissimus dorsi flap reconstruction for scalp coverage, both requiring intraoperative and continuous postoperative vasopressor support to maintain adequate blood flow through the recipient artery. These cases add to the growing literature that vasopressors are safe in microsurgery, as they demonstrate vasoactive medications can be a useful tool to improve blood flow in recipient vessels in head and neck microsurgery, and not merely to maintain systemic pressures intraoperatively.…”
mentioning
confidence: 99%